Two-level factorial design of the pre-processing activities of polyamide 12 powder in selective laser sintering three-dimensional printing process - Muhamad Damanhuri, Amir Abdullah; Hariri, Azian; Ab Ghani, Sharin; Md Fauadi, Muhammad Hafidz Fazli; Hussin, Mohamed Saiful Firdaus (2020)
Powder exposure during selective laser sintering (SLS) three-dimensional (3D) printing process is detrimental to the health of workers in the indoor workspace and those in surrounding areas. To date, there is a paucity of studies concerning the factors involved in the SLS 3D printing process that have a significant effect on the indoor air concentrations. Hence, in this study, two-level factorial design was conducted to identify the factors that have a significant effect on the indoor air concentrations (particulate matter with a diameter less than 2.5 and 10.0 μm (PM2.5 and PM10), ultrafine particles (UFP), and total volatile organic compounds (TVOC)) during pre - processing activities of the SLS 3D printing process. The exposure during handling of polyamide 12 (PA12) was simulated in a 24-m2 SLS 3D printing chamber. The following factors were investigated: (1) Factor A (air velocity (fan speed of the split air conditioner), (2) Factor B (refresh rate (the use of recycled PA12 powder), (3) Factor C (collecting powder from the mixing machine), (4) Factor D (transferring powder to the SLS 3D printing machine), and (5) Factor E (pouring powder into the feeder chamber). The sampling methods were conducted according to the Industry Code of Practice on Indoor Air Quality, Department of Occupational Safety and Health, Malaysia. Based on the analysis of variance results, Factor B was the most significant factor that contributed to the PM2.5, PM10, UFP, and TVOC concentrations during the pre-processing activities of the SLS 3D printing process. In conclusion, proper handling and the use of an automated vacuum conveying technology for the pre-processing activities will help prevent the spreading of gaseous and aerosol particles to other areas within vicinity of the SLS 3D printing process.